The Implementation of Lean Management in Accelerating Health Insurance Claim Process at Hospitals - Elisabeth Lia Friskasari; Chriswardani Suryawati; Henry Setyawan (Universitas Muhammadiyah Yogyakarta, 2019)
Due to the changing payment system of healthcare services in the era of National Health Insurance from fee for service to be INACBGs (Indonesian Case Base Groups), health care financing system has changed from fee for service to INACBGs (Indonesian Case Base Groups) package system. In this case, hospitals especially the private ones, must have a stable financial capacity to be able to survive and operate. One of efforts to overcome this issue is to improve efficiency in all aspects and to make the claim submission on time. A continous improvement effort is needed to identify waste and improve the efficiency of a process, one of which is application of Lean Management. This study aimed to identify waste which can delays the process of claim submission. This study was conducted at a private hospital in Central Java. The research is a qualitative research with descriptive analytic methods. The result showed that the waste in the outpatient claim process was 52,4% and the waste in the inpatient claim process was 52,2 % of all activities. The implementation of lean management for the process of health insurance claims was estimated to reduce the time cycle of outpatient claim process from 97.018 seconds to 181 seconds and the time cycle of inpatient claim process from 109.897 seconds to 406 seconds.